Bioengineering measures for stabilising cut slopes of Dipayal-Mallekh road, Far Western Nepal - Ojha, Gobinda; Shrestha, Raju (Bulletin of the Department of Geology, 2008)
The Dipayal-Mellekh road is considered as one of the major infrastructures of the northern region of Doti District as it is only the motorable access. The road extends for about 40 km and is 8 m wide. It passes through six Village Development Committees. This paper describes possibility of using Plantation as a treatment option to safeguard the road and reduce long term maintenance. The study shows that roadside slope instabilities and erosion problems exist in the road alignment due to presence of highly weathered rocks and high cut slope angles. On the basis of slope length, slope angle, material drainage, and site moisture condition, the erosion control measures were suggested. Jute netting with grass lines plantation, site seedling of shrub and trees, vegetated gabion wall, brush layering, palisades, live check dam and fascines are recommended bio-engineering measures for controlling instabilities and erosion problems along the road. doi: 10.3126/bdg.v10i0.1423 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 79-88